Assessment of Colobanthus quitensis genetic polymorphism from the Argentine Islands region (maritime Antarctic) by actin, α- and γ-tubulin gene intron analysis - A. Rabokon; A. Postovoitovа; Yu. Bilonozhko; L. Kalafat; M. Pavlovska; Ie. Prekrasna; I. Parnikoza; I. Kozeretska; Ya. Pirko; Ya. Blume (Ukrainian Antarctic Journal, 2020)
Colobanthus quitensis is one of the two angiosperm plant species commonly spread in the Antarctic. The species has been extensively analyzed at morphological, anatomical and physiological levels, but information regarding its genetic variability remains limited. The aim of the study was to identify molecular genetic differences between C. quitensis populations in one of the Antarctic localities, the Argentine Islands region by estimating the intron length polymorphism of actin, α- and γ-tubulin genes. Samples of C. quitensis from different Antarctic natural populations were collected during the season of the 24th and previous Ukrainian Antarctic expeditions. Total DNA was isolated using the QIAGEN DNeasy Plant Mini Kit. The polymerase chain reaction was carried out with our own degenerate primers. The resulting amplicons were separated and visualized using polyacrylamide gel electrophoresis followed by silver nitrate staining. Molecular genetic analysis of natural populations of C. quitensis was performed using three DNA-marker systems based on the detection of intron length polymorphism of actin, α- and γ-tubulin genes. A low level of genetic  polymorphism of C. quitensis in the studied region by these types of markers was established. By assessing the intron length polymorphism of actin genes of the studied C. quitensis populations it was possible to establish that the populations of Skua Island had unique amplicons characteristic only for this location. This indicates the possibility of further use of the analysis of intron length polymorphism of actin genes for the study of the molecular genetic diversity of the Antarctic pearlwort. At the same time, the results of analysis of the intron length polymorphism of α- and γ-tubulin genes induce selection of more specific primers, taking into account the structure of the C. quitensis genome. C. quitensis in the study region has a low level of genetic variability in intron length polymorphism of actin, α- and γ-tubulin genes. Overall, the results indicate that DNA markers based on gene structure analysis of highly conserved cytoskeletal proteins, namely, actin, α- and γ-tubulin, as additional sources of information, can be used for molecular genetic analysis of C. quitensis populations in the Antarctic.